PENINGKATAN KOMPETENSI GURU BAHASA INDONESIA DALAM MENERAPKAN PROSES BELAJAR MENGAJAR SESUAI RPP MELALUI SUPERVISI AKADEMIK DI KELAS VIII SMP KATOLIK VIRGO FIDELIS MAUMERE - MARIA TATIANA ERTI, (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2020)
One of the main problems in formal education learning today is the low quality of learning that results from the preparation of the teacher. The implementation of learning can be successful when preceded by planning a learning program that serves to provide direction to the entire teacher is to develop a learning implementation plan (RPP) which can be used as a guideline in the teaching process. The problems faced so far that the teachers are drafting RPP is still limited to fulfilling administrative tasks and implementation in the classroom is often not in accordance with the steps specified or designed in the RPP. This certainly contradicts the RPP function itself which is the teacher's teaching guideline. This certainly contradicts the RPP function itself which is the teacher's teaching guideline. Facing this fact, the academic supervision carried out by the headmaster may help to improve the competency of the religious teacher who is the beginner teacher at SMPK Virgo Fidelis in drafting learning planning and implementing learning according to the planned learning implementation plan. Based on the results of the research that has been outlined, researchers can conclude that: (1) The ongoing academic supervision can improve the competence of Indonesian teacher in grade VIII SMPK Virgo Fidelis Maumere in implementing the teaching and learning process according to RPP(2) The increase in competency of Indonesian teachers in applying appropriate learning with the RPP can be illustrated through the observation results of the following researchers: (1) cycle I by number 19 score, percentage of value is 52.7% and is in the category less; (2) cycle II with a score of 26, percentage of the value is 72.22% and is in the category insufficient; (3) Cycle III with the number of 28 scores, percentage of value 77.77% and is in the category good. From this data it proved that between cycle conditions I and II increased by 19.45% and between cycle II and III increased by 5.55%.